(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: The primary objectives of the study was to determine the chronotropic response to exercise and heart rate recovery in young adults. METHODOLOGY: A descriptive cross-sectional study was conducted on 377 young healthy adults, belonging to the age range of 18-24 years. The population was recruited from the Foundation University School of Health Sciences. Screening of participants was performed using the PAR-Q+ questionnaire, while BMI, waist-hip ratio, resting blood pressure, and heart rate were measured. Warm-up was performed, followed by a 3-minute step test using a 12-inch step. Lastly, blood pressure and heart rate were recorded again after activity cessation at 1 min, 2 min, and 3 min. RESULTS: The mean and corresponding standard deviations for heart rate, HR resting was 94.39 ± 12.55, HR peak was 139.85 ± 19.08, HR_1 min was 136.98 ± 20.12, and HR_2 min was 116.03 ± 16.30, HR_3 min 98.61 ± 12.97. Healthy young individuals showed a mean Chronotropic Index of 48.05 ± 11.25, all of the participants reported to be chronotropically incompetent, i.e., 100%. The mean heart rate recovery of the total sample was 27.72 ± 11.60. About 260 participants reported normal heart rate recovery, i.e., 69%, and 117 showed abnormal heart rate recovery, i.e., 31%, respectively. CONCLUSION: The results of the current study concluded that the heart rate recovery of young, healthy adults during 3-minute step testing was found to be normal in the majority of participants, whereas the chronotropic response of all participants was found to be incompetent.